Використання селективних еталонних зображень в оптичному діапазоні для систем навігації керованих об'єктів - Юзефович, В.Б.; Мезенцев, О.В.; Буточнов, О.М.; Цибульська, Є.О. (Реєстрація, зберігання і обробка даних, 2019)
Продемонстровано можливість і доцільність використання селективних або бінарних селективних зображень як еталонних зображень оптичного діапазону для вирішення задач кореляційно-екстремальної навігації літальних апаратів (ЛА) Проаналізовано кореляційні характеристики оптичних зображень без спеціальної обробки, селективних у градаціях сірого та бінарних селективних зображень. Показано, що бінарні селективні зображення мають найкращі кореляційні характеристики, однак для їхнього використання необхідна наявність швидких методів формування селективних поточних зображень на борту ЛА. Продемонстрирована возможность и целесообразность использования селективных изображений или бинарных селективных изображений в качестве эталонных изображений оптического диапазона для решения задач корреляционно-экстремальной навигации летательных аппаратов (ЛА). Проанализированы корреляционные характеристики оптических изображений без специальной обработки, селективных изображений в градациях серого и бинарных селективных изображений. Показано, что бинарные селективные изображения имеют лучшие корреляционные характеристики. однако для их использования необходимо наличие быстрых методов формирования селективных изображений на борту ЛА A possibility (an advisability under certain conditions) to use various types of optical range images as the reference image to solve the problems of the correlation-extremal guidance of the controlled aerial vehicles is considered. During the flight the correlation-extremal navigation (guidance) system performs a comparison of reference images of sighting surface, prepared before, and current images from the onboard sensors. To form optimal reference images the correlation characteristics of the regular optical images, selective grayscale images and binary images are analyzed. It is shown that the selective images with sufficient number of stable informative features are characterized by most «quality» cross-correlation function (it has a lower level of «background» and a more intense main peak). This approach potentially increases the quality of the solution of controlled objects navigation (guidance) problems on the basis of such images. On addition, the advantage of using selective reference images is the small amount of memory required to store them and lower bandwidth requirements of communication channels for their transmission. Also there is considered the use of binary selective current images with binary selective reference images to solve the problems of the correlation-extremal guidance of the controlled aerial vehicles. It is shown that it is necessary to use fast methods of selective images formation (to obtain selective current images on a board) and to apply the methods of temporary objects removing on the input images (for example, on the base of common analysis of the few images of the sighting surface obtained in a different time) to prepare the reference images with stable information features for increasing of the navigation (guidance) accuracy.